Preclinical evaluation of a fully-human, quadrivalent-hantavirus polyclonal antibody derived from non-human source. - Dr Jay Hooper; Dr Steve Kwilas; Dr Rebecca Brocato; Mr. Matthew Josleyn; Ms. Lucia Principe; Mr Joshua Shamblin; Dr. Hua Wu; Dr. Christoph Bausch; Dr. Tom Luke; Dr Priya Karmali; Mr. Jerel Vega; Dr Padmanabh Chivukaula; et al. (International Journal of Infectious Diseases)
Background: Hantaviruses are rodent-borne viruses that can cause severe disease in infected humans. In the New World, major hantaviruses include Andes virus (ANDV) and Sin Nombre virus (SNV), and the disease is known as hantavirus pulmonary syndrome (HPS). In the Old World, major hantaviruses include Hantaan virus (HTNV) and Puumala virus (PUUV), and the disease is known as hemorrhagic fever with renal syndrome (HFRS). Previously, transchromsomic bovines (TcBs) were used and engineered to produce fully human antibodies to produce anti-HPS human polyclonal neutralizing antibody (SAB-400) that protected Syrian hamsters against lethal disease caused by ANDV and SNV; and anti-HFRS human polyclonal neutralizing antibody, SAB-159 and SAB-159P, that protected hamsters against infection with HTNV and PUUV, respectively. Methods & Materials: Here, the same approach was used to produce a candidate cGMP product (SAB-163) targeting both HFRS and HPS. Two TcB animals were produced and qualified for cGMP antibody manufacturing. One animal was vaccinated with a lipid nanoparticle (LNP)-formulated ANDV and a SNV M gene-based DNA vaccine and a second animal was vaccinated with LNP-formulated HTNV and PUUV DNA vaccine. The hantavirus M gene encodes the viral envelop glycoproteins. The resultant fully-human, polyclonal antibody purified from the combined plasma from the two TcBs was designated SAB-163. Results: SAB-163 has potent neutralizing antibodies (PRNT50 >200,000) against the four targeted hantaviruses, and cross-neutralization against several other heterotypic hantaviruses, albeit with lower titers. SAB-163 was tested for safety in a GLP toxicity study in rabbits and human tissue binding study and was found to be safe. SAB-163 was tested for efficacy in Syrian hamsters. At a dosage of 10 mg/kg, SAB-163 is bioavailable in hamsters out to 70 days post-treatment with a half-life of 10-15 days. At this same dosage, SAB-163 administered 1 day or out 5 days after exposure protected all hamsters from lethal disease caused by ANDV. At a higher dose, partial protection was achieved as late as day 6 in the ANDV model. SAB-163 also protected hamsters in the HTNV, PUUV, and SNV infection models when administered 1 day before or up to 3 days after challenge. Conclusion: The candidate product is attractive because it is fully-human, polyclonal, safe and effective in animal models, and was produced from plasma collected within ∼100 days without the use of blood products from HFRS or HPS patients. Essentially, the virus sequence information was transformed into a candidate human polyclonal antibody product capable of protecting against prototype hantaviruses from Asia, Europe, and the Americas.